INTEGRATION BETWEEN FINANCIAL TECHNOLOGY AND BUSINESS PROCESS RE-ENGINEERING TO ENHANCE BANKING EFFICIENCY: AN EXPLORATORY STUDY - Mustafa Salam Abdulrida; Ghazwan Ayad Khalid Al-Shiblawi; Rafid Kadhim Nsaif AL-obaidi (Scholars Digest Publishing, 2023)
This paper mainly aims to clarify the role and importance of financial technology variables and process re-engineering as the most important basic pillars in the banking business and the extent of reliance on them in supporting the bank's performance in a way that enhances banking efficiency and enhances the service level of banks and enables the bank to provide high-quality services suitable for financial modernity. The research relies on the analytical descriptive approach in studying the various aspects of financial technology, re-engineering, and banking efficiency, and testing the research hypothesis through a 28-items questionnaire. The data were analyzed according to the statistical program (SPSS), as well as measuring the validity and reliability of the questionnaire by testing the degree of credibility with Cronbach's alpha coefficient for testing and measuring the degree of credibility (reliability) in the responses received on the questionnaire questions. The research problem lies in the statement of the effect of the variables of financial technology and process re-engineering in enhancing banking efficiency, based on which the alternative hypothesis was accepted. The results show that there is an important role in the integration of financial technology and re-engineering in providing banks with high efficiency. Therefore, financial technology innovations should be employed and a sound administrative environment should be provided that contributes significantly to enhancing banking efficiency to achieve high-quality banking services.
Keywords: Financial Technology, Process Re-Engineering, Banking Efficiency, Financial Performance.